2008
DOI: 10.1088/0022-3727/41/24/245402
|View full text |Cite
|
Sign up to set email alerts
|

The compensation source in nitrogen doped ZnO

Abstract: Nitrogen doped zinc oxide (ZnO) films have been prepared by molecular beam epitaxy. The as-grown samples show n-type conduction, but they convert to p-type after being annealed in O2 atmosphere. X-ray photoelectron spectroscopy reveals that the conversion is mainly caused by the escaping of substituted N molecule (N2)O donors from the films, and photoluminescence spectroscopy confirms the extraction of (N2)O. The work shown in this paper reveals experimentally that the main compensation source in nitrogen dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In literature, N‐induced modifications of defects/defect complexes in ZnO have been investigated using different spectroscopic techniques . The Raman mode near 275 cm −1 is known to be due to atomic nitrogen in the vacant oxygen sites (N O ) in ZnO .…”
Section: Introductionmentioning
confidence: 99%
“…In literature, N‐induced modifications of defects/defect complexes in ZnO have been investigated using different spectroscopic techniques . The Raman mode near 275 cm −1 is known to be due to atomic nitrogen in the vacant oxygen sites (N O ) in ZnO .…”
Section: Introductionmentioning
confidence: 99%
“…All these results show the high efficiency of SPT in depositing the p-type ZnO films compared with other deposition techniques like: sol-gel [45], chemical vapor deposition (CVD) [46][47][48], sputtering [49], atomic layer deposition (ALD) [11,50] and molecular beam epitaxy (MBE) [13,51].…”
Section: Electrical Propertiesmentioning
confidence: 84%
“…However, this hindrance has been overcome by the selection of deposition techniques. Among the successful deposition techniques [10][11][12][13] in obtaining p-type ZnO, spray pyrolysis technique (SPT) made significant contribution with encouraging results [14][15][16][17][18][19]. However, achieving the final goal of producing stable ptype ZnO remains huge challenge.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 Among different possible acceptor dopants for ZnO, nitrogen has been regarded as one of the most suitable acceptors due to its similar atomic size and electronic structure to oxygen, 3 and hence, it has been extensively studied. [5][6][7][8][9][10][11][12][13][14][15][16] However, p-type conductivity in N:ZnO remains controversial. 3,4 Recent theoretical calculations indicated that nitrogen is a deep acceptor, 5 although hole binding energy derived from PL experiments on N:ZnO was comparable to that observed for Mg in GaN, 4 indicating that nitrogen is a shallow acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to other compensating donors present in undoped ZnO, nitrogen molecules at an oxygen site (N 2 ) O are also donors, 3,4,7,8 so that the choice of nitrogen source has a significant influence on the doping. P-type conductivity in N:ZnO, grown by variety of methods and with different nitrogen sources, has been reported to date.…”
Section: Introductionmentioning
confidence: 99%